Flipbook-Based Digital Comics: Learning Outcomes and Attitudes of Elementary School Students - Rodhotul Janah; Kurotul Aeni (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study aims to develop, assess the feasibility, and evaluate the effectiveness of the Flipbook-Based Digital Comics to Improve Learning Outcomes and Attitudes of Grade IV Students. Methodology: The research employed a Research and Development (R&D) method using the Borg & Gall development model up to the eighth stage. The subjects of this study were 28 Grade IV students at Elementary School Tambangan 01 Semarang. Data analysis techniques included media feasibility assessments, teacher and student response analyses, normality testing, t-tests, and N-Gain evaluation. Main Findings: Based on the results obtained, flipbook-based digital comic media can be used in learning activities. Flipbook-based digital comic learning media is effectively used in learning grade IV material on attitudes and behavior that reflect the practice of Pancasila in social life. The results of the validation assessment of media experts and material experts obtained a percentage of 83.33% and 100% which means it has a very feasible classification level. The student pretest score was 55% and the posttest score was 86.13%. The percentage of student learning outcomes classically increased by 31.13%. Novelty/Originality of this study: The novelty of this research lies in the media Flipbook-Based Digital Comics to Improve Learning Outcomes and Attitudes. In addition, the learning model has been adjusted to students’ abilities and uses HOTS (Higher Order Thinking Skills) based evaluation questions.